LITERATURE REVIEW ON THE OVERVIEW OF RISK FACTORS OF SEVERE PREECLAMPSIA IN PREGNANT WOMEN - Solehati, Tetti; Andini, Melina Rike; Triesna, Meuthia Saulikha; Zaenal, Zabina Syaharani; Iqroansyah, Rifa Ikbal; Sakti, Dimas Wibawa; Kosasih, Cecep Eli (Journal of Maternity Care and Reproductive Health, 2024)
Severe preeclampsia (PEB) is one of the causes of maternal death. Pregnant  mothers  must have adequate knowledge about dangerous risk factors during pregnancy, especially PEB, so that they can manage a safe pregnancy to prevent and minimize maternal or infant death. Objective: to identify risk factors for severe preeclampsia in pregnant women. Method: This research design uses a literature review by collecting articles from databases and search engines such as; PubMed, Garuda, Semantic Scholar, Neliti, and EBSCO use the keywords "pregnant women", AND "risk factors", AND "severe preeclampsia", and in Indonesian, "pregnant women" AND "risk factors" AND "severe preeclampsia". Articles were filtered based on inclusion criteria including: pregnant women as subjects, descriptive research methods, cross-sectional, English or Indonesian language, and full text in the period 2011 and 2021. A total of 5 articles were selected, and analysis was carried out. Results: Risk factors that influence the incidence of PEB in pregnant women are: maternal age, parity, education level, gestational age, history of PEB, history of DM, socio-economics, frequency of ANC, and weight gain. Meanwhile, factors that do not influence the incidence of PEB are work and the distance between pregnancies. Conclusion: Many factors influence the risk of preeclampsia. Therefore, it is recommended to provide education about prevention efforts to pregnant women who have risk factors for severe preeclampsia in their pregnancy.